2010
DOI: 10.1371/journal.pone.0011151
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Lithium Sensitivity and Regulation of Inositol Biosynthetic Genes

Abstract: Lithium (Li+) is a common treatment for bipolar mood disorder, a major psychiatric illness with a lifetime prevalence of more than 1%. Risk of bipolar disorder is heavily influenced by genetic predisposition, but is a complex genetic trait and, to date, genetic studies have provided little insight into its molecular origins. An alternative approach is to investigate the genetics of Li+ sensitivity. Using the social amoeba Dictyostelium, we previously identified prolyl oligopeptidase (PO) as a modulator of Li+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 47 publications
0
41
0
1
Order By: Relevance
“…qPCR was performed exactly as previously described (75). Expression levels were normalized to Ig7 as a loading control and calculated relative to wild-type controls.…”
Section: V-atpasementioning
confidence: 99%
“…qPCR was performed exactly as previously described (75). Expression levels were normalized to Ig7 as a loading control and calculated relative to wild-type controls.…”
Section: V-atpasementioning
confidence: 99%
“…Subsequent studies demonstrated that PREP was a negative regulator of inositol (1,4,5)-trisphosphate (IP 3 ) synthesis, a Li + sensitive intracellular signalling molecule [9,10] . It was shown in Dictyostelium and in cultured human cells that PREP could act via the enzyme multiple inositol polyphosphate phosphatase (Mipp1) to control gene expression and hence affect the level of the second-messenger IP 3 [9] . This was an indication of the existence of a novel gene regulatory network modulating inositol metabolism and hence Li + sensitivity.…”
mentioning
confidence: 99%
“…In another pathway analysis approach, King et al [43] undertook a genetic screen for Li resistance in the social amoeba Dictyostelium in hopes of deciphering the molecular basis for Li's effectiveness as a mood stabilizer. Prolyl oligopeptidase -an enzyme altered in bipolar disorder patients -is a modulator of Li sensitivity and a negative regulator of inositol(1,4,5)trisphosphate (IP3) synthesis, a Li-sensitive intracellular signal.…”
Section: Expression Studiesmentioning
confidence: 99%
“…Prolyl oligopeptidase -an enzyme altered in bipolar disorder patients -is a modulator of Li sensitivity and a negative regulator of inositol(1,4,5)trisphosphate (IP3) synthesis, a Li-sensitive intracellular signal. The authors showed that in Dictyostelium, as well as in cultured human cells, prolyl oligopeptidase acts via multiple inositol polyphosphate phosphatase (Mipp1) to modulate Li sensitivity through a gene-regulatory network that converges on inositol metabolism [43]. Kubota …”
Section: Expression Studiesmentioning
confidence: 99%